The Assumption of Equal Marginal Utility of Income: How Much Does it Matter? - Hege Medin; Karine Nyborg; Ian Bateman (Statistics Norway, Research Department, 1998)
In most applied cost-benefit analyses, individual willingness to pay is aggregated without using explicit welfare weights. This can be justified by postulating a utilitarian social welfare function, along with the assumption of equal marginal utility of income for all individuals. However, since marginal utility is a cardinal concept, there is no generally accepted way to verify the plausibility of this latter assumption, nor its empirical importance. In this paper we use data from seven contingent valuation studies to illustrate that if one instead assumes equal marginal utility of the public good for all individuals, aggregate monetary benefit estimates change dramatically.
Keywords: D61; D62; D63; H41; Q2; 330; Utility comparisons; environmental valuation; cost-benefit analysis; choice of numeraire